2021
DOI: 10.1109/access.2021.3081138
|View full text |Cite
|
Sign up to set email alerts
|

Robust Array Beamforming via an Improved Chicken Swarm Optimization Approach

Abstract: Robust array beamforming is a challenging task in radar, sonar and communications due to the influence of direction of arrival (DOA) mismatch and sensor position errors. However, how to enhance the robustness of beamforming is a key issue in antenna arrays. The current paper focuses on a novel approach called the improved chicken swarm optimization (ICSO) method to settle the optimization model of conventional linearly constrained minimum variance (LCMV) based on support vector machine (SVM) to against the mis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…As mentioned above, recent studies [ 13 , 14 , 15 , 16 , 17 , 21 , 22 , 23 , 24 ] through simulation have observed that artificial intelligence and precisely bio-inspired techniques are preferable to traditional probabilistic and deterministic approaches subject to optimizing the energy consumption in IoT networks. In [ 17 , 21 ], the authors proved the proposed algorithm based on CSO obtains excellent performance over traditional approaches such as PSO, FL and GA for robust beam-forming approach, whereas authors in papers [ 24 , 25 ] CSO-based clustering routing protocol plays a significant role in reducing energy consumption over integration with bio-inspired approaches.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…As mentioned above, recent studies [ 13 , 14 , 15 , 16 , 17 , 21 , 22 , 23 , 24 ] through simulation have observed that artificial intelligence and precisely bio-inspired techniques are preferable to traditional probabilistic and deterministic approaches subject to optimizing the energy consumption in IoT networks. In [ 17 , 21 ], the authors proved the proposed algorithm based on CSO obtains excellent performance over traditional approaches such as PSO, FL and GA for robust beam-forming approach, whereas authors in papers [ 24 , 25 ] CSO-based clustering routing protocol plays a significant role in reducing energy consumption over integration with bio-inspired approaches.…”
Section: Related Workmentioning
confidence: 99%
“…Recent studies have shown that meta-heuristics approaches are more suitable for approximately solving NP problems for CH selection [ 20 ]. Consequently, proper optimization methods such as fuzzy logic inference [ 13 , 14 ], bat algorithm [ 15 ], particle swarm optimization [ 16 , 17 , 18 ], differential evolutionary and harmony search [ 19 , 20 ], genetic algorithm (GA) [ 21 ], and bio-inspired chicken swarm optimization (CSO) have the potential to be effectively used for finding the optimal number of CHs [ 22 , 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%